Chinese Entrepreneurs, the Party-State, and Gender: Women Succeed in Business without the CCP. (November 2022) - Chen, Minglu; Goldsmith, Benjamin E.; Ratcliff, Shaun
Abstract: In this article, we take a gender perspective to explore the relationship between private entrepreneurs' business success and their Chinese Communist Party (CCP) membership. We theorize that, due to male-dominated CCP-business networks, female entrepreneurs are not able to leverage CCP membership into greater business success. Observable implications of this are that women will experience little or no business advantage from Party membership, while men will experience a significant advantage. The independence of women's business success from Party connections allows the possibility that women have carved out an area of autonomy from the party-state. Using a series of national entrepreneur surveys collected between 2002 and 2012, we assess the degree of empirical support for our expectations. We show that the CCP does appear to function as an exclusive "boys' club" in terms of profitable patronage or networks, while the most successful women tend not to be Party members. The surveys also provide some evidence consistent with a CCP effort to recruit successful female entrepreneurs in order to curtail their autonomy. Our findings suggest non-CCP female entrepreneurs are a significant but generally overlooked socio-economic group with considerable potential autonomy.